“Shakunakharas": - Shruti Pant Banerjee; Hari Priya Pathak (Sanglap: Journal of Literary and Cultural Inquiry)
The oral culture of the Central Himalayan region of Kumaun survives mainly due to its folk songs, which represent the true spirit of Kumauni life by reflecting the daily struggles, beliefs and superstitions, customs and rituals, and the popular legends and myths of the region. However, there are a variety of folk songs which are sung on specific occasions and have a particular social function. In the following paper, we have attempted to present the translations of some of these popular folk ritual songs called the Shakunakharas.